ICT as a Component of Knowledge Economy Development of Western Balkan Countries - Nedic, Vladimir M; Cvetanović, Slobodan Ž; Despotovic, Danijela Zoran (Industrija, 2014)
Based on the measurement of World Bank Institute's knowledge economy index (KAM), this paper researches the achieved level of ICT application in four Western Balkan countries (Albania, Bosnia and Herzegovina, Macedonia and Serbia) and six selected EU neighbouring countries (Austria, Bulgaria, Greece, Croatia, Romania, Slovenia). Correlation analysis was used to research the interdependence of ICT and other KEI pillars, and GDP per capita at global level and in ten observed countries. Afterwards, depth of the gap of the ICT application level was identified by using the cluster and radar chart analyses among ten selected European countries placed into two groups (Western Balkan countries and their neighbouring countries).Finally, using the overtime comparison model of the most recent available data and data from year 2000, the trend of the change of key variables' values of ICT pillar in Western Balkan countries and neighbouring EU countries was additionally researched. The conclusion arises that the determined gap in ICT application between Western Balkan countries and  selected EU countries means, per se, that these countries relatively lag behind in knowledge economy development, and, moreover, they lag behind in the development of information society in general.
Keywords: ICT; EU countries; Western Balkan; Economy; Knowledge